The Role of Hospital Management Information Systems in Enhancing Compliance with Surgical Site Infection Prevention Protocols: A Systematic Review - Nurhadi Nurhadi; Endang Triyanto (Indonesian Journal of Global Health Research, 2025)
Surgical Site Infections (SSIs) remain a significant challenge in hospital settings, affecting patient safety and increasing healthcare costs. The implementation of Hospital Management Information Systems (HMIS) has been proposed as a strategy to enhance compliance with infection prevention protocols among healthcare professionals. However, variations in adherence and technological adoption remain a concern. Objective: This study aims to assess the impact of HMIS on nurses’ compliance with infection prevention protocols in surgical settings by synthesizing existing research evidence. Method: A systematic literature review was conducted following PRISMA guidelines. Peer-reviewed studies published between 2019 and 2024 were analyzed, focusing on HMIS implementation, infection control compliance, and hospital-acquired infection (HAI) reduction. Results: The findings suggest that HMIS improves real-time monitoring, documentation accuracy, and adherence to infection control protocols. However, challenges such as workload, training gaps, and system integration issues hinder optimal compliance. Conclusion: HMIS plays a crucial role in enhancing infection prevention measures in hospitals. Future research should explore long-term effectiveness, cost-efficiency, and the integration of artificial intelligence to further optimize digital health interventions for infection control.